2017
DOI: 10.1016/j.jes.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reclaimed water effluent on bacterial community structure in the Typha angustifolia L. rhizosphere soil of urbanized riverside wetland, China

Abstract: In order to evaluate the impact of reclaimed water on the ecology of bacterial communities in the Typha angustifolia L. rhizosphere soil, bacterial community structure was investigated using a combination of terminal restriction fragment length polymorphism and 16S rRNA gene clone library. The results revealed significant spatial variation of bacterial communities along the river from upstream and downstream. For example, a higher relative abundance of γ-Proteobacteria, Firmicutes, Chloroflexi and a lower prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Similarly to the current research, Proteobacteria has been reportedly dominant in CWs in previous studies [33,60], mainly composed of organisms able to perform heterotrophic denitrification [62]. The decrease in Proteobacteria corresponds to the fate of rhizospheric Proteobacteria in the presence of FQ and other unknown antibiotics as described by previous reports [13,23,63]. The decreased abundance of Proteobacteria indicates denitrification had been profoundly prohibited in tank 1 over the experimental period, during which time the process might continue normally in tank 2 as discussed in Section 4.2.…”
Section: Effect Of Enrofloxacin On Microbial Communitiessupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly to the current research, Proteobacteria has been reportedly dominant in CWs in previous studies [33,60], mainly composed of organisms able to perform heterotrophic denitrification [62]. The decrease in Proteobacteria corresponds to the fate of rhizospheric Proteobacteria in the presence of FQ and other unknown antibiotics as described by previous reports [13,23,63]. The decreased abundance of Proteobacteria indicates denitrification had been profoundly prohibited in tank 1 over the experimental period, during which time the process might continue normally in tank 2 as discussed in Section 4.2.…”
Section: Effect Of Enrofloxacin On Microbial Communitiessupporting
confidence: 87%
“…As an innovative variant of CWs, floating treatment wetlands (FTWs) have also been widely utilized for their better performance, greater flexibility in applications and even lower costs [10][11][12]. With roots as the filter substrate, rhizospheric microorganisms play a crucial role in the removal of contaminants by the FTW [13,14]. However, microbial activity, composition and diversity in terrestrial and aquatic environments have been seriously affected in the presence of antibiotics [15,16] usually used by humans in clinical therapy to annihilate or prevent the growth of bacteria or as prophylaxes and growth promotors in animal husbandry [17].…”
Section: Introductionmentioning
confidence: 99%
“…HTS has been used to investigate microbial ecology under fertilization and RW irrigation, including the effects of secondary soil salinization and acidification due to high N application rates on bacterial community composition [16]. Bacterial community structure and biochemical cycling capacity of contaminants in wetlands were shown to be altered under RW irrigation [17]. Research has further shown negative effects on microbial activity as a result of N amendment [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, microbial nitri cation and denitri cation is believed to be the primary pathway in this process (Kuypers et al, 2018). Compared to archaea and fungi, bacteria have more diverse N-cycling related genes expressed in higher quantities, which play an imperative role in the N removal process, especially amongst rhizosphere bacteria (Huang et al, 2017). The rhizosphere is an active, complex ecosystem where plant root exudates, composed of a wide variety of molecules are released from the plant into the rhizosphere (Wu et al, 2017), with consequences to the assembly of rhizospheric soil microbial communities.…”
Section: Introductionmentioning
confidence: 99%